2019
DOI: 10.1111/tbed.13163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effectiveness of Mass Vaccination Campaign against Peste des petits ruminants in Chhattisgarh state, India

Abstract: Summary The study evaluated the effectiveness of ‘Mass Vaccination Campaign (MVC)’ implemented against the contagious transboundary OIE notified Peste des petits ruminants (PPR) in sheep and goats on the lines of ‘pulse polio campaign’ for humans in Chhattisgarh state, India. The effectiveness was evaluated on the axes of adequacy, financial viability under with and without MVC through differencing under various scenarios and options and programme impact from a farmer's perspective. The adequacy evaluation rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Regardless of whether 30% or 100% of animals were vaccinated in subsequent years, the benefits outweighed the costs. The results provide a reference for the implementation of a mass vaccination campaign in India or other countries with similar socioeconomic environments and small ruminant production systems [70].…”
Section: Research Advances To Inform Evidence-based Ppr Control and Vmentioning
confidence: 94%
See 1 more Smart Citation
“…Regardless of whether 30% or 100% of animals were vaccinated in subsequent years, the benefits outweighed the costs. The results provide a reference for the implementation of a mass vaccination campaign in India or other countries with similar socioeconomic environments and small ruminant production systems [70].…”
Section: Research Advances To Inform Evidence-based Ppr Control and Vmentioning
confidence: 94%
“…To maximize the economic benefits of PPR control and eradication, vaccination programs require careful planning using scientific evidence. In India, three axes of PPR mass vaccination campaign, namely, adequacy (vaccination coverage, number of outbreaks, diagnosed and death cases, and vaccination seroconversion), financial viability (program under different scenarios and options), and the program impact from farmers' perspective were evaluated [70]. The study showed that the reported outbreaks, diagnosed and death cases declined in consonance with increased vaccination coverage.…”
Section: Research Advances To Inform Evidence-based Ppr Control and Vmentioning
confidence: 99%
“…Moreover, neither systematic surveillance nor sero-monitoring was undertaken to assess the effectiveness of the vaccination in a particular region except for a few studies (Balamurugan et al, 2018(Balamurugan et al, , 2020b. The disease has been brought under control in some of the states and PPR outbreaks threat reported declined progressively and substantially in the continuous vaccination practiced states like Chhattisgarh (Balamurugan et al, 2018) and Southern peninsular region (Balamurugan et al, 2020b) and benefits outweigh the cost of a vaccination program (Govindaraj et al, 2019).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Te analysis of PPR epidemic situation and trends in the disease spread in recent years in neighboring countries indicates a considerable threat of PPR introduction in Kazakhstan. Epidemic situation in Mongolia and China, as well as in Georgia, Turkey, and Iran, is of particular importance [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%